Progressive Christianity from the Perspective of Constructive-Decolonial Theology: A Mirror of Liminal Space for Contemporary Theology - Tampilang, Risno (Jurnal Pendidikan Agama Kristen (JUPAK), 2024)
The emergence of the progressive Christian movement has sparked controversy and is considered a deviation from traditional Christian teachings. However, on the other hand, progressive Christianity is also seen as an effort to contextualize the Christian faith within the ever-evolving realities of the times. This research uses a qualitative method with a descriptive approach to illustrate the phenomenon of progressive Christianity. The aim of this study is to explore progressive Christianity and its development from the perspective of constructive-decolonial theology, thereby opening a more constructive paradigm in line with contemporary human life. Progressive Christianity is viewed as a "liminal space," or between old traditions and renewal in contemporary Christian theology. Constructive-decolonial theology are used as perspectives to understand progressive Christianity, where constructive theology encourages the Christian faith to exhibit dynamic openness. Progressive Christianity is a movement that has emerged in response to social, cultural, and theological changes. Openness and willingness to listen to and engage in constructive dialogue amidst differences are necessary, making liminality a space for ongoing theological creativity and transformation.